2018
DOI: 10.3389/fimmu.2018.00893
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor-γ Modulates the Response of Macrophages to Lipopolysaccharide and Glucocorticoids

Abstract: Although glucocorticoids (GC) represent the most frequently used immunosuppressive drugs, their effects are still not well understood. In our previous studies, we have shown that treatment of monocytes with GC does not cause a global suppression of monocytic effector functions, but rather induces differentiation of a specific anti-inflammatory phenotype. The anti-inflammatory role of peroxisome proliferator-activated receptor (PPAR)-γ has been extensively studied during recent years. However, a relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(93 citation statements)
references
References 63 publications
5
88
0
Order By: Relevance
“…The scRNA‐seq assay reveals that hemocytes express markers such as Integrin alphaPS2 (If), EcR/Hr96, Lamp1, Rgh, Tfc/lectin‐46Cb/CG34033, and Lz, which are the Drosophila orthologues of CD11b, PPARγ, CD68, Dectin, CD207, and RUNX, respectively. In mammals, these proteins are responsible for migration, adhesion, phagocytosis, differentiation from monocytes to macrophages, and pathogen recognition (Ramprasad et al , ; Voon et al , ; Podolnikova et al , ; Daley et al , ; Heming et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The scRNA‐seq assay reveals that hemocytes express markers such as Integrin alphaPS2 (If), EcR/Hr96, Lamp1, Rgh, Tfc/lectin‐46Cb/CG34033, and Lz, which are the Drosophila orthologues of CD11b, PPARγ, CD68, Dectin, CD207, and RUNX, respectively. In mammals, these proteins are responsible for migration, adhesion, phagocytosis, differentiation from monocytes to macrophages, and pathogen recognition (Ramprasad et al , ; Voon et al , ; Podolnikova et al , ; Daley et al , ; Heming et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that PPARG agonists inhibit the production of pro-inflammatory cytokines, such as TNF-α, IL-1β, and IL-6 38 . Macrophages loss of PPARG leads to altered differentiation kinetics 39 . PPARG has been described to be important for resolving inflammation and maintaining homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of PPARγ by Pioglitazone, which inhibits NF-κB-mediated transcription [2], may prevent the induction of such endotoxin tolerance by inhibiting the initial TLR-dependent NF-κB activation and thus resulting in an increased TNFα production by macrophages in Pioglitazone-fed mice that are challenged with LPS. Exacerbating the effects of overproduction of TNFα by liver macrophages in this system could be the reciprocal decrease in anti-inflammatory IL-10 production by macrophages [28], that has been reported to be able to significantly reduce or even prevent GalN/LPS-induced liver injury [29]. Conversely, inhibiting PPARγ via antagonist administration could reverse this situation, possibly leading to a protective effect in GalN/LPS-induced liver injury.…”
Section: Discussionmentioning
confidence: 94%